Relapsing polychondritis that developed after piercing (clinical case) - A. A. Movsesyan; S. O. Krasnenko; M. M. Urumova; A. A. Godzenko (Современная ревматология, 2023)
Relapsing polychondritis (RPC) belongs to a group of rare rheumatic diseases with poorly understood etiology and pathogenesis. It is based on progressive systemic inflammatory damage to the cartilage tissue, primarily affecting ears, nose, trachea and bronchi. A standardized approach for the treatment of RPC has not yet been developed, so the treatment tactics are individualized for each patient.We describe a clinical case of a 39-year-old patient, who developed RPC after piercing the cartilaginous part of the ear. The components of the alloy used for the piercing could presumably serve as adjuvants and cause the development of a disease similar to ASIA syndrome (Autoimmune/Inflammatory Syndrome Induced by Adjuvants) with inflammation of the cartilage of the nose and ears. Possible pathogenetic mechanisms are presented, as well as diagnostic criteria for ASIA syndrome.